Homologous recombination changes the context of Cytochrome b transcription in the mitochondrial genome of Silene vulgaris KRA - Štorchová, Helena; Stone, James D; Sloan, Daniel B; Abeyawardana, Oushadee A J; Müller, Karel; Walterová, Jana; Pažoutová, Marie (BMC genomics, 2018)
BACKGROUND: Silene vulgaris (bladder campion) is a gynodioecious species existing as two genders - male-sterile females and hermaphrodites. Cytoplasmic male sterility (CMS) is generally encoded by mitochondrial genes, which interact with nuclear fertility restorer genes. Mitochondrial genomes of this species vary in DNA sequence, gene order and gene content. Multiple CMS genes are expected to exist in S. vulgaris, but little is known about their molecular identity. RESULTS: We assembled the complete mitochondrial genome from the haplotype KRA of S. vulgaris. It consists of five chromosomes, two of which recombine with each other. Two small non-recombining chromosomes exist in linear, supercoiled and relaxed circle forms. We compared the mitochondrial transcriptomes from females and hermaphrodites and confirmed the differentially expressed chimeric gene bobt as the strongest CMS candidate gene in S. vulgaris KRA. The chimeric gene bobt is co-transcribed with the Cytochrome b (cob) gene in some genomic configurations. The co-transcription of a CMS factor with an essential gene may constrain transcription inhibition as a mechanism for fertility restoration because of the need to maintain appropriate production of the necessary protein. Homologous recombination places the gene cob outside the control of bobt, which allows for the suppression of the CMS gene by the fertility restorer genes. We found the loss of three editing sites in the KRA mitochondrial genome and identified four sites with highly distinct editing rates between KRA and another S. vulgaris haplotypes (KOV). Three of these highly differentially edited sites were located in the transport membrane protein B (mttB) gene. They resulted in differences in MttB protein sequences between haplotypes. CONCLUSIONS: Frequent homologous recombination events that are widespread in plant mitochondrial genomes may change chromosomal configurations and also the control of gene transcription including CMS gene expression. Posttranscriptional processes, e.g. RNA editing shall be evaluated in evolutionary and co-evolutionary studies of mitochondrial genes, because they may change protein composition despite the sequence identity of the respective genes. The investigation of natural populations of wild species such as S. vulgaris are necessary to reveal important aspects of CMS missed in domesticated crops, the traditional focus of the CMS studies.
Keywords: otevřené čtecí rámce; homologní rekombinace; cytochromy b; RNA Editing; Mitochondria; Genome, Mitochondrial; Silene; Membrane Glycoproteins; Plant Proteins; neplodnost rostlin; Cytochromes b; genom mitochondriální; rostlinné proteiny; Homologous Recombination; mitochondrie; Mitochondrial Proton-Translocating ATPases; Plant Infertility; Haplotypes; editace RNA; mitochondriální protonové ATPasy; transkriptom; membránové glykoproteiny; haplotypy; Open Reading Frames; Transcriptome